Effects of obstacle angle on methane–air deflagration characteristics in a semi-confined chamber. (January 2017) - Wen, Xiaoping; Ding, Haoqing; Su, Tengfei; Wang, Fahui; Deng, Haoxin; Zheng, Kai
Abstract: A semi-confined transparent chamber, with a square cross-section of 150 × 150 mm 2 and a height of 500 mm, was constructed to assess the effects of different obstacle angle on the characteristics of methane–air deflagrating flame. Nine cases, with different obstacle angles (30, 60, 90, 120, and 150°) but with the same obstacle length or same blockage ratio respectively, were studied. The results indicate that if the obstacle length is constant, it takes the shortest time for the case with the largest obstacle angle to reach the obstacle, but its flame acceleration is not as evident as that of the cases with smaller angles in the latter stages. The case with 90° obstacle angle produces the highest peak overpressure of 126 mbar. Comparatively, the peak overpressure approximately decreases by 38%, 17%, 11%, and 32% in the cases with obstacle angle of 30, 60, 120, and 150°, respectively. At the same blockage ratio, increasing the obstacle angle decreases the time from ignition to the peak overpressure but increases the peak overpressure. In addition, for the obstacles with the same obstacle angle, the larger the blockage ratio is, the lower the maximum flame speed. Highlights: Nine configurations with different obstacle angles are investigated. High-speed flame images and overpressures were recorded and analyzed. Obstacle angles have significant effects on deflagration characteristics. The case with 90° angle produces the highest overpressure. Increasing the blockage of the obstacle decreases the maximum flame speed.